2021
DOI: 10.1016/j.ihj.2020.11.150
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of Late Gadolinium Enhancement by Cardiac MRI in risk stratification of heart failure patients with moderate and severe LV dysfunction

Abstract: Objective This is a prospective study of patients with LVEF ≤40%, with the objective of correlating CV events to LGE detected and quantified by CMRI. Methods Heart Failure (HF) patients with LVEF <40% who underwent CMRI were included. LGE volume of ≥6% of the myocardial volume was considered significant. Data of appropriate ICD shocks, CV hospitalizations and mortality were recorded. Results There were 133 HF (72 ICM & 62 NIDCM) patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Late gadolinium enhancement (LGE) in cardiac MRI (CMRI ) has proven to be a reliable surrogate of myocardial scar which is the essential substrate for sudden death and worsening HF. 1, 2 Detailed imaging inputs from CMRI have helped to precisely define the endocardial and epicardial scar, assess accurately the ventricular function, and finely delineate the arrythmogenic channels in the substrate. Further it has aided substantially in prognostication in patients with substrates like hypertrophic cardiomyopathy and non-ischemic cardiomyopathy (NICM).…”
mentioning
confidence: 99%
“…Late gadolinium enhancement (LGE) in cardiac MRI (CMRI ) has proven to be a reliable surrogate of myocardial scar which is the essential substrate for sudden death and worsening HF. 1, 2 Detailed imaging inputs from CMRI have helped to precisely define the endocardial and epicardial scar, assess accurately the ventricular function, and finely delineate the arrythmogenic channels in the substrate. Further it has aided substantially in prognostication in patients with substrates like hypertrophic cardiomyopathy and non-ischemic cardiomyopathy (NICM).…”
mentioning
confidence: 99%
“…In this cohort, 44/46 CV events were seen in patients who had LGE over the cut off level. 8 Patients presenting to ER with resuscitated cardiac arrest are a difficult substrate as many do not have easily identifiable or modifiable substrates. Data with CMI has shown that identification of scar in these patients can help to optimally use the defibrillators.…”
mentioning
confidence: 99%